Noble gas composition, cosmic-ray exposure age, 39Ar-40Ar, and I-Xe analyses of ungrouped achondrite NWA 7325 - Hopp, Jens; Meyer, Hans-Peter; Trieloff, Mario (Meteoritics & planetary science, 2018)
Northwest Africa (NWA) 7325 is an anomalous achondrite that experienced episodes of large-degree melt extraction and interaction with melt under reducing conditions. Its composition led to speculations about a Mercurian origin and provoked a series of studies of this meteorite. We present the noble gas composition, and results of 40Ar/39Ar and 129I-129Xe studies of whole rock splits of NWA 7325. The light noble gases are dominated by cosmogenic isotopes. 21Ne and 38Ar cosmic-ray exposure ages are 25.6 and 18.9 Ma, respectively, when calculated with a nominal whole rock composition. This 38Ar age is in reasonable agreement with a cosmic-ray exposure age of 17.5 Ma derived in our 40Ar/39Ar dating study. Due to the low K-content of 19 ± 1 ppm and high Ca-content of approximately 12.40 ± 0.15 wt%, no reliable 40Ar/39Ar age could be determined. The integrated age strongly depends on the choice of an initial 40Ar/36Ar ratio. An air-like component is dominant in lower temperature extractions and assuming air 40Ar/36Ar for the trapped component results in a calculated integrated age of 3200 ± 260 (1σ) Ma. This may represent the upper age limit for a major reheating event affecting the K-Ar system. Results of 129I-129Xe dating give no useful chronological information, i.e., no isochron is observed. Considering the highest 129Xe*/128XeI ratio as equivalent to a lower age limit, we calculate an I-Xe age of about 4536 Ma. In addition, elevated 129Xe/132Xe ratios of up to 1.65 ± 0.18 in higher temperature extractions indicate an early formation of NWA 7325, with subsequent disturbance of the I-Xe system.
Gesehen am 11.06.2019
Im Titel sind die Zahlen 39 und 40 als Hochzahlen dargestellt